Western Ukraine in the Context of Disintegration and Integration Processes During the 1930s-1940s (historical and legal aspect) - Andriy Redko (Vasyl Stefanyk Precarpathian National University, 2019)
In this article the disintegration and integration processes in Central and Eastern Europe and their influence on the legal status of Western Ukraine are researched. Disintegration correlates with the Soviet occupation of Western Ukraine, and integration correlates with the process of its joining the USSR. The historical and legal dimension of Ukraine in the European context is conceptualized by distinguishing the stages of these processes.